Strategi Pengelolaan Hutan Mangrove dengan Analisis SWOT di Desa Sei Naga Lawan Kecamatan Perbaungan Kabupaten Deli Serdang - Sirait, Firli Nur Afdilla; Luluk, Theresia Angeline; Geubrina, Pocut Puan; Harefa, Melinda (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Coastal ecosystems are strategic transition zones between land and sea. It supports the ecological, economic and social aspects of society. It is in this zone that mangrove forests grow as the most productive ecosystem. Sei Naga Lawan Mangrove Village Beach is located in Perbaungan District, Deli Serdang Regency. The area is utilized for tourism, fishing, and non-timber products. However, its management still faces several challenges. Local regulations on mangroves are still limited. Community participation has not been optimized. Sustainability strategies have not been well mapped. These conditions demand in-depth research. This research focuses on Sei Naga Lawan Village. It aims to explore sustainable mangrove forest management strategies. This research uses a descriptive qualitative approach that aims to describe mangrove forest management strategies and community participation in its utilization in Sei Naga Lawan Village, Perbaungan District, Deli Serdang Regency. With data collection techniques including observation, interviews, and documentation. Observations were conducted to obtain a direct picture of the physical conditions and community activities. The variables in this study consist of independent variables, namely management strategies and community participation, and dependent variables, namely the impact on the economy of coastal communities. Data analysis was conducted descriptively through data reduction, data presentation, and conclusion drawing. To support the interpretation of the results, SWOT analysis was also used to identify strengths, weaknesses, opportunities, and threats in mangrove forest management in the research location.